Method for the study of real rights: Curriculum with a global organic approach - García Sánchez, Arán (2025)
The traditional study of real rights has been shaped by a unidirectional conception derived from dominium, focused on the subject-holder and object relationship. This approach, rooted in 19th-century categories, has hindered the analysis of complex contemporary legal realities. To address this shortcoming, an organic-global methodological approach is proposed—one that analyzes real rights based on the complex legal relationship, integrating its structural elements (subjective, objective, and causal). This proposal arises from the critical analysis of law school curricula from leading faculties in Spain and Mexico, where the persistence of static theoretical models was identified. Its goal is to reform legal education through a critical and organic mindset that goes beyond merely describing entitlements and instead examines interactions between ownership, propter rem duties, and erga omnes guarantees. It also seeks to foster the development of professional competencies that provide tools for resolving complex property-related situations.